2008
DOI: 10.1124/dmd.108.025155
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Vitamin D Receptor Inhibition of Cholesterol 7α-Hydroxylase Gene Transcription in Human Hepatocytes

Abstract: ABSTRACT:Lithocholic acid (LCA) is a potent endogenous vitamin D receptor (VDR) ligand. In cholestasis, LCA levels increase in the liver and intestine. The objective of this study is to test the hypothesis that VDR plays a role in inhibiting cholesterol 7␣-hydroxylase (CYP7A1) gene expression and bile acid synthesis in human hepatocytes. Immunoblot analysis has detected VDR proteins in the nucleus of the human hepatoma cell line HepG2 and human primary hepatocytes. 1␣, 25-Dihydroxy-vitamin D 3 or LCA acetate-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 40 publications
1
79
0
1
Order By: Relevance
“…Although the expression level of VDR is not especially high in human hepatocytes, 41,42) it has been reported that the activation of VDR led to modifications in the expression of hepatic CYPs, such as CYP3A4, 8) CYP7A1 and CYP24A1, 10) and to altered hepatic lipid metabolism. 43) The previous and present findings therefore suggest that HPL-A3 is a useful tool for the screening of hVDR activators/inhibitors and for the analysis of hVDR function in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the expression level of VDR is not especially high in human hepatocytes, 41,42) it has been reported that the activation of VDR led to modifications in the expression of hepatic CYPs, such as CYP3A4, 8) CYP7A1 and CYP24A1, 10) and to altered hepatic lipid metabolism. 43) The previous and present findings therefore suggest that HPL-A3 is a useful tool for the screening of hVDR activators/inhibitors and for the analysis of hVDR function in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…6,7) Likewise, vitamin D receptor (VDR) 8) and constitutive androstane receptor (CAR), 9) which also act as a transcriptional activators of CYP3A subfamily genes, are expressed at low levels or not at all in human hepatoma-derived cell lines, including HepG2. 5,10) Recently, several stable cell lines for a human PXR (hPXR)-based reporter gene assay for the screening of CYP3A4 inducers have been established by co-transfection into human cell lines of an hPXR expression vector and a plasmid containing a reporter gene and hPXR-binding elements. [11][12][13][14][15] However, the available data on the xenobiotic-mediated induction of CYP3A enzymes at the levels of mRNA and activity in the reported cell lines are limited.…”
mentioning
confidence: 99%
“…Expression plasmids for CBP and Gal4-CBP were gifts from Dr. Carolyn Smith (Baylor College of Medicine, Houston, TX). Plasmids for peroxisome proliferatoractivated receptor ␥ co-activator 1␣ (PGC1␣), Gal4-PGC1␣, Gal4-steroid receptor co-activator (SRC1), and Gal4-SRC2 were generated as reported previously (29).…”
Section: Methodsmentioning
confidence: 99%
“…All primers/probe sets for real-time PCR were ordered from TaqMan Gene Expression Assays (Applied Biosystems, Foster City, CA). For assay of ROR␣ and GAPDH mRNA, SYBR Green primers (Applied Biosystems) were used as reported previously (29). Amplification of ubiquitin C and GAPDH were used as internal controls.…”
Section: Rna Isolation and Quantitativementioning
confidence: 99%
“…The secondary bile acid LCA is a ligand of PXR and VDR. These two receptors bind to the BARE-I sequence in the human CYP7A1 promoter and inhibit CYP7A1 promoter activity ( 131,132 ). PXR interacts with HNF4 ␣ and blocks HNF4 ␣ recruitment of PGC-1 ␣ to CYP7A1 chromatin and results in inhibiting CYP7A1 transcription.…”
Section: Fxr-independent Bile Acid Inhibition Of Cyp7a1mentioning
confidence: 99%